Geometric Morphometric Analyses Support Incorporating the Goshen Point Type into Plainview. Issue 1 (January 2020) - Buchanan, Briggs; Collard, Mark; O'Brien, Michael J.
Abstract : Recent work has demonstrated that Goshen points overlap in time with another group of unfluted lanceolate points from the Plains, Plainview points. This has raised the question of whether the two types should be kept separate or consolidated into a single type. We sought to resolve this issue by applying geometric morphometric methods to a sample of points from well-documented Goshen and Plainview assemblages. We found that their shapes were statistically indistinguishable, which indicates that Goshen and Plainview points should be assigned to the same type. Because Plainview points were recognized before Goshen points, it is the latter type name that should be dropped. Sinking Goshen into Plainview allows us to move beyond taxonomic issues and toward understanding both the spatiotemporal variation that exists among Plainview assemblages and what it can tell us about the adaptations and social dynamics of Plainview groups.